2008
DOI: 10.1016/j.nurt.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Therapeutics for Dystonia

Abstract: Summary: Dystonia is a neurological syndrome characterized by excessive involuntary muscle contractions leading to twisting movements and unnatural postures. It has many different clinical manifestations, and many different causes. More than 3 million people worldwide suffer from dystonia, yet there are few broadly effective treatments. In the past decade, progress in research has advanced our understanding of the pathogenesis of dystonia to a point where drug discovery efforts are now feasible. Several strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 92 publications
(109 reference statements)
0
30
0
Order By: Relevance
“…It has been suggested that several forms of dystonia may have shared etiologies [13][14][15] and therefore may respond to the same therapeutic intervention. Although the primary cause for the signs and symptoms of dystonia may differ, there are several reasons to suspect a common underlying process [6]. Thus, treatments aimed at downstream targets might prove effective across multiple etiologies and allow for broader subject inclusion based on phenotype rather than etiology.…”
Section: Clinical Characteristics Of Dystonia and Associated Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that several forms of dystonia may have shared etiologies [13][14][15] and therefore may respond to the same therapeutic intervention. Although the primary cause for the signs and symptoms of dystonia may differ, there are several reasons to suspect a common underlying process [6]. Thus, treatments aimed at downstream targets might prove effective across multiple etiologies and allow for broader subject inclusion based on phenotype rather than etiology.…”
Section: Clinical Characteristics Of Dystonia and Associated Challengesmentioning
confidence: 99%
“…A high-throughput screen conducted in a Caenorhabditis elegans model of DYT1 dystonia has revealed potential agents for further study, such as ampicillin [23]. Other promising agents have been identified through pharmacological studies of rodent models of dystonia, including the dystonic dt sz hamster and tottering mouse models [6,24]. Whether or not these agents are effective for patients with dystonia remains to be determined.…”
Section: Potential Sources Of Novel Dystonia Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main symptoms, which can be mild or severe, include involuntary muscle contraction and uncontrollable twisting of the affected body part (eyelids, neck, face, hand, foot). The exact causes of dystonia are still elusive, but it has been linked to communication problems with neurons located in the basal ganglia [31]. The first most frequent indication of botulinum toxin treatment among focal dystonias is cranial dystonia, notably blepharospasm, sometimes bruxism, trismus, oromandibular dystonia and rarely lingual dystonia.…”
Section: The Revelation Of the Swan: Clinical Exploitation Of The Musmentioning
confidence: 99%
“…Mammalian models are invaluable tools for examining the DYT gene products, especially considering the wide range of clinical features associated with dystonia, such as muscle contraction, tremors, and/or myoclonus [3][4][5], that may illustrate under-explored aspects of neuronal misregulation. Nevertheless, these models may not recapitulate all pathological impairments of dystonia and are expensive.…”
Section: Introductionmentioning
confidence: 99%